2014
DOI: 10.35648/20.500.12413/11781/ii200
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Security in Respecting and Protecting the Dignity of Lone Mothers in South Africa: Final Report

Abstract: This chapter provides details about the research methods that were used in the project as well as the principles of ethical research that informed each stage of the project. Details are provided about the focus groups, in-depth interviews, elite interviews, and modules in the South

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…In less vulnerable households, the CSG facilitated recipients' investments in their children's education, and offered the promise of children's material conditions being better than their own. Wright et al (2014a) also found the CSG was enabling dispersal of children among households -for example to access better educational provision in urban areas. Mothers (typically) would claim the grant for their non-co-resident children and remit to an urban relative with whom the child actually lived.…”
Section: Income Poverty and Social Protection For Vulnerable Childrenmentioning
confidence: 93%
See 4 more Smart Citations
“…In less vulnerable households, the CSG facilitated recipients' investments in their children's education, and offered the promise of children's material conditions being better than their own. Wright et al (2014a) also found the CSG was enabling dispersal of children among households -for example to access better educational provision in urban areas. Mothers (typically) would claim the grant for their non-co-resident children and remit to an urban relative with whom the child actually lived.…”
Section: Income Poverty and Social Protection For Vulnerable Childrenmentioning
confidence: 93%
“…He'll say: "what kind of mother are you, you can't even give me R1?" [...] Poverty destroys our dignity as mothers' (Wright et al, 2014a).…”
Section: Children's and Young People's Experiences Of Povertymentioning
confidence: 99%
See 3 more Smart Citations